Parasitoides de ovos de Tibraca luibativentris stal (Hemiptera: pentatomidae) no cultivo de arroz no Estado do Maranhão - Machado, Keneson Klay Gonçalves (2013)
The rice stink bug (Tibraca limbativentris) is a mains phytophagous insects of in irrigated fields and dry land. The damage caused by this insect pest render the production and reduce grain yield. Currently the control of T. limbativentris restricted only to applications of pesticides, so there is need to use other control methods less harmful to the environment. So, the study aimed to identify and to quantify the parasitoids eggs of T. limbativentris in rice cultivation in the state of Maranhão. The research was conducted in rice crops in the municipalities of Arari, Miranda North, North Matões and Santa Rita during the years 2010, 2011 and 2012 and in the Entomology Laboratory at the State University of Maranhão Campus St. Louis. Were performed collection of egg masses during the months of March, April, May, June and July, during the years 2010, 2011 and 2012. We evaluated the number of eggs collected, number of parasitized eggs, number of parasitoids emergeds, eggs parasitism, parasitoids species, correlation between eggs collected and parasitoids emergeds a function of temperature and precipitation and the dependent relationship between the number of eggs collecteds and parasitoids emergeds. Of 3.810 eggs collected from T. limbativentris found that 1.178 eggs were parasitizeds. Were identified in the research three species of eggs parasitoids Telenomus podisi, Trissolcus urichi and Ooencyrtus submetallicus. The parasitism rate of eggs collected in the municipalities of Arari, Matões North and Miranda do Norte were 35.32%, 35.07% and 26.76%, respectively, with the most common parasitoids in the study areas were species Telenomus podisi and Trissolcus urichi. It is concluded that the use of eggs parasitoids for the biological control of T. limbativentris should be seen as an important practice to be incorporated into integrated pest management in rice cultivation